Performance Of Balitbangtan Native Chicken With Various Level of Leucaena leucocephala Leaf Flour in Feeds: PERFORMA AYAM KUB DENGAN BERBAGAI LEVEL TEPUNG DAUN LAMTORO (LEUCAENA LEUCOCEPHALA) DALAM PAKANNYA - Krishaditersanto, Rip; Mulyanti, Eni (Universitas Djuanda, 2023)
Feed is the largest production input at the farm, include in native chiken farm. Ingredieent of feed devine in two part, there are as resource energy and resoursce protein. Protein source feed are relatively more expensive than energy source. Lamtoro leaves (Leucaena leucocephala) is a legume source of protein that can grow well in tropical and dry climates. The crude protein content of lamtoro leaf flour can reach above 20% so that it has the potential as a protein source feed ingredient for chicken livestock. This research was conducted to determine the level of proportion of lamtoro leaf meal in chicken feed, in this case the Balitbangtan superior native chicken (KUB) without affecting its performance. The combination of 4 treatments with different proportions of lamtoro leaf meal in the feed, namely P0 = 0%, P1 = 5%, P2 = 10% and P4 = 15%, with each treatment consisting of 3 groups containing 5 KUB chickens aged 4 weeks with initial body weight 247 – 255 g. Length of maintenance/research 8 weeks (up to 12 weeks of age). Parameters observed were feed consumption, final body weight, daily body weight growth, and feed conversion. The results showed that there was no significant difference between treatments (P>0.05) both in the level of feed consumption, daily body weight gain, and feed conversion. It can be concluded that lamtoro leaf flour can be used up to a level of 15% in the grower phase of KUB chicken livestock rations.